Air assisted in situ upgrading via underground heating for ultra heavy oil: Experimental and numerical simulation study. (1st November 2020) - Pei, Shufeng; Cui, Guodong; Wang, Yanyong; Zhang, Liang; Wang, Qiaobo; Zhang, Panfeng; Huang, Lijuan; Ren, Shaoran
Highlights: Air injection assisted in situ upgrading process (ISU) of ultra heavy oils was proposed. The effect of air injection on heat transfer was studied. The influence of low temperature oxidation on oil cracking was investigated. The benefit of air injection on energy efficiency of the ISU process was evaluated. Abstract: In situ upgrading (ISU) via underground heating and thermal cracking is regarded as an effective technique for exploiting ultra heavy oils, in which the heavy oil components can be cracked into light oils and gases for production. However, the slow heating rate via conduction from wellbore to oil formation is the main issue concerned in the conventional ISU process. Herein, an air injection assisted ISU technique (AAISU) is proposed to improve heat transfer by gas convection and along with the thermal effect of oil oxidation due to the oxygen in the injected air. Air injection can also provide extra energy for oil production and reservoir pressure maintenance. To illustrate the advantage of the proposed AAISU technique, thermal cracking experiments of ultra heavy oil samples in the presence of air under high pressure were conducted to investigate the reaction mechanisms and to establish the kinetics models of the oxidation and cracking reactions. Moreover, reservoir numerical simulation studies are performed to evaluate the effects of air injection during the ISU process. The experiment results indicate that the ultra heavy oil can be effectively cracked into gases, light oils and coke-like substances in the presence of air at temperature over 350 °C. The activation energy of the thermal cracking derived is around 248 kJ/mol. The numerical simulation results show that the heat transfer rate can be effectively enhanced by air injection because of the heat convection of the air flow and the thermal effect of the low temperature oxidation reactions of oil components. The total oil recovery factor can be increased via air injection with improved energy conversion efficiency from 6.51 GJ/GJ to 8.42 GJ/GJ.